DIGITALIZATION OF AGRICULTURAL LAND UTILIZATION FOR FOOD AND ENERGY SECURITY AS A DRIVER OF THE SHARIA ECONOMY - Aristianti, Aulia Intan; Prasetyomukti, Rihadatul Aisah; Anti, Windhi Widhi; Listiyani, Silviya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The development of digital technology has opened up new opportunities for more effective and sustainable agricultural land use, thus addressing the challenges of food and energy security in Indonesia. This study aims to explore a model for implementing digitalization in the agricultural sector that not only focuses on increasing productivity but also integrates renewable energy management as part of the sharia economic ecosystem. The research method used is a qualitative approach with literature studies and descriptive analysis of digital technology implementation models, such as the Internet of Things (IoT), big data analytics, and digital-based sharia financing platforms, in agricultural land use. The results of the study indicate that technology can increase the efficiency of agricultural production and strengthen the position of farmers in the sharia economic value chain. To support national food security, BNI implements agricultural digitalization through various services, such as the Farmer Card for fertilizer, empowerment of Fertilizer Kiosks, and digital People's Business Credit (KUR) facilities, which aim to increase farmer productivity. With the right strategy, state revenue can be increased without sacrificing long-term social and economic stability, and support sustainable digitalization in the agricultural sector. The implications of this study indicate that agricultural digitalization, when integrated with the sharia economic ecosystem, can be a key driver in creating an inclusive and sustainable food system.